Pelatihan dan Pendampingan Aparatur Desa dalam Pembentukan Koperasi Desa Merah Putih di Desa Sena - Herkules Herkules; Amalia Akita; Aditiya Pratama Daryana; Vina Gabriella Saragih (BADAN PENERBIT STIEPARI PRESS, 2025)
The training and mentoring of Desa Sena’s village apparatus in establishing the Merah Putih Village Cooperative were driven by the national priority of empowering village economies through healthy and accountable cooperative institutions. This study aimed to enhance the technical capacity and regulatory literacy of village officials in drafting foundational cooperative documents, facilitating the legalization process, and monitoring the sustainability of cooperative operations. Methods included intensive socialization and training on cooperative concepts and the latest regulations, technical field mentoring for drafting the Articles of Association/Bylaws and preparing the General Meeting of Members, and post-legalization monitoring and evaluation through group discussions. Findings revealed the completion of comprehensive Articles of Association drafts, the democratic election of cooperative management, and the formulation of a medium-term business development roadmap. Implications underscore improved effectiveness in village cooperative governance and recommend a sustainable mentoring model for replication in other villages.